2019
DOI: 10.25082/swsw.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Motivated by a mandate: a university-clinic partnership to develop a perinatal depression registry at a community based hospital in the Midwest

Abstract: Disparities in maternal mental health outcomes persist despite the myriad of existing evidence based treatments and recent public health prevention policy efforts. Integrated health care delivery models such as Collaborative Care and patient medical home models have the potential to reduce health disparities in clinic settings. These evidence-based approaches require multidisciplinary teams for successful implementation and to provide quality care to improve specified patient outcomes. However, strategies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Within Illinois, past studies found that the rates of depressive symptoms and suicidal ideation detected on depression screens can be higher for low-income populations and racially minoritized populations ( 17 , 18 ). Mandates for depression screening can be effective to motivate clinicians and health care systems to adopt screening practices ( 19 , 20 ). Screening remains an essential approach to identify those in need of mental health care ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within Illinois, past studies found that the rates of depressive symptoms and suicidal ideation detected on depression screens can be higher for low-income populations and racially minoritized populations ( 17 , 18 ). Mandates for depression screening can be effective to motivate clinicians and health care systems to adopt screening practices ( 19 , 20 ). Screening remains an essential approach to identify those in need of mental health care ( 21 ).…”
Section: Discussionmentioning
confidence: 99%